Piperine Plays an Anti-Inflammatory Role in Staphylococcus aureus Endometritis by Inhibiting Activation of NF-κB and MAPK Pathways in Mice. (12th May 2016) - Zhai, Wen-jun; Zhang, Zhen-biao; Xu, Nian-nian; Guo, Ying-fang; Qiu, Changwei; Li, Cheng-ye; Deng, Gan-zhen; Guo, Meng-yao
Abstract : Endometritis is commonly caused by pathogenic microorganisms, including Staphylococcus aureus ( S. aureus ). Piperine, which is a natural medicine, has shown a variety of biological activities. To explore the effect and mechanism of piperine on S. aureus endometritis, a mouse model of S. aureus endometritis was successfully established in the present study. Histopathological changes were observed with H&E staining, cytokines were analyzed by ELISA, mRNA was analyzed by qPCR, and proteins were detected by western blot. The results showed that piperine could significantly alleviate inflammatory injury in S. aureus endometritis. The qPCR and ELISA results showed that piperine effectively reduced the S. aureus -induced overexpression of TNF- α, IL-1 β, and IL-6 but increased the expression of IL-10. The S. aureus -induced inflammation was related to TLR-2 and TLR-4 because the results showed that their expression was increased in S. aureus infection but then decreased with piperine treatment. To further confirm that piperine caused an anti-inflammatory response by targeting NF- κ B and MAPKs, the expression of I- κ B, p65, p38, ERK, and JNK was measured. The phosphorylation of I- κ B, p65, p38, ERK, and JNK was inhibited by piperine in a dose-dependent manner. All of the results indicated that piperine may be a potential anti-inflammatory drug both in endometritis and in other S. aureus -induced diseases.